Analisis Tingkat Pemahaman dan Miskonsepsi Anak Asuh tentang Fotosintesis di Panti Asuhan Al-Ihsan Banjarmasin - Gusti Hadiatus Solehah (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Photosynthesis is one of the fundamental concepts in science education that students need to understand because it is closely related to food production and oxygen supply for life on Earth. This study aimed to analyze students' understanding of the basic concepts of photosynthesis and identify the misconceptions they still possess. The study employed a descriptive qualitative approach using interviews with five students based on ten questions related to photosynthesis. The collected data were analyzed descriptively according to the accuracy of students' responses for each indicator. The results showed that most students had understood the basic concepts of photosynthesis, particularly its definition, the primary organ where photosynthesis occurs, the role of chlorophyll, the time when photosynthesis takes place, and its importance for life. However, several misconceptions were identified regarding the gases involved in photosynthesis, the main products of the process, the source of energy used, and the plant organ responsible for water absorption. These findings indicate that photosynthesis instruction should be strengthened through contextual learning, inquiry-based approaches, simple laboratory activities, and the use of engaging instructional media to improve students' conceptual understanding and reduce misconceptions.